2013
DOI: 10.3109/03639045.2013.819880
|View full text |Cite
|
Sign up to set email alerts
|

A simple pharmacokinetic model of alendronate developed using plasma concentration and urine excretion data from healthy men

Abstract: The study of pharmacokinetics of alendronate has been hampered by difficulties in accurately and reproducibly determining their concentrations in serum and urine. Thus, pharmacokinetic characteristics of alendronate have been described in many reports based on urinary excretion data; and plasma pharmacokinetics and the simultaneous pharmacokinetic models of alendronate in plasma and urine are not available. The aims of this study were to measure alendronate concentration in plasma and excretion in urine concur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 16 publications
0
17
0
Order By: Relevance
“…After administration, BPs distribute in plasma and consequently retain in the bone by approximately 60% (Chae et al., ; Chen et al., ; Khan et al., ; Kozloff et al., ; Sato et al., ). In the mandible, BP deposits on the alveolar bone and bone surrounding the periodontal ligament of molar roots (Kozloff et al., ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…After administration, BPs distribute in plasma and consequently retain in the bone by approximately 60% (Chae et al., ; Chen et al., ; Khan et al., ; Kozloff et al., ; Sato et al., ). In the mandible, BP deposits on the alveolar bone and bone surrounding the periodontal ligament of molar roots (Kozloff et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…After administration, BPs distribute in plasma and consequently retain in the bone by approximately 60% (Chae et al, 2014;Chen et al, 2002;Khan et al, 1997;Kozloff et al, 2010;Sato et al, 1991).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We selected urine sampling times based on previously published urinary excretion data for rifampin, and chose a time point for evaluation in the validation study based on diagnostic accuracy in healthy subjects. In future work we will employ optimal sampling theory to identify urine sampling schemes that predict serum pharmacokinetics better than a single 4-h timed void [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…Little is known about urinary excretion in long term, and only the experimental Frontiers in Bioengineering and Biotechnology frontiersin.org data obtained by Khan et al (1997) could be found to validate these specific results. The experimental data from Chae et al (2014) were used to adjust the serum concentration in short term, while those obtained by Kang et al (2006) were used for the short-term urinary excretion. Other authors measured similar values for both types of results (Cocquyt et al, 1999;Acotto et al, 2012).…”
Section: Pharmacokineticsmentioning
confidence: 99%